ANALISIS PENGARUH SUKU BUNGA SERTIFIKAT BANK INDONESIA DAN JUMLAH UANG BEREDAR TERHADAP TINGKAT INFLASI DI INDONESIA PERIODE 2006.1-2015.12 (PENDEKATAN ERROR CORRECTION MODEL) - D.A. Dwi Rahmawati; Wahyu Hidayat Riyanto (Program Studi Ekonomi Pembangunan, 2017)
Prominent characteristics of the direction economic policy in Asia is the emphasis on the inflation rate. Inflation is defined as a condition increases the price of prevailing goods in an economy continuously. The purpose of this research is to find out and analyze the influence of Bank Indonesia Certificate interest rate and money supply toward the inflation rate in Indonesia. This research method using time series of monthly data during the period of the 2006.1-2015.12 model approach using error correction (ECM) in the long term or short term. The results of the estimation of cointegration equation indicate that on the long run variable Bank Indonesia Certificate interest rate and money supply is significantly effected by to the inflation rate in Indonesia. While ECM model is considered valid because the error correction term (ECT) has significant value. In the short term only Bank Indonesia Certificate interest rates that influence significantly to the inflation rate in Indonesia. Keywords: inflation, interest rates, money supply, error correction model